Trinity Western University v The Law Society of Upper Canada: 2018 SCC 33: Supreme Court of Canada: McLachlin CJ, Abella, Moldaver, Karakatsanis, Wagner, Gascon, Côté, Brown, and Rowe JJ: 15 June 2018. (11th October 2018) - Bussey, Barry W
Abstract: Constitutional law – Canadian Charter of Rights and Freedoms – Freedom of conscience and religion – Interference with – Private religious university (TWU) sought accreditation for a new law school from Canadian Federation of Law Societies – Law Society of Upper Canada (LSUC) denied accreditation on grounds of TWU's code of conduct prohibiting sexual intimacy outside of traditional marriage – TWU claiming judicial review of Law Society's decision on grounds of breach of religious freedom – Ontario Divisional Court and Ontario Court of Appeal refusing claim – TWU appealing to Supreme Court – Whether Law Society decision reasonable within the Doré/Loyola administrative law framework giving deference to original decision maker in accordance with decision maker's expertise – Whether Law Society entitled to take into account admissions policy of law school – Whether there had been a proportionate balance of Charter protections and statutory objectives—Canadian Charter of Rights and Freedoms, Part I of the Constitution Act 1982, being sch B to the Canada Act 1982 (UK), 1982, ch 11, preamble, ss 1, 2(a) - Law Society Act, RSO 1990, c L.8, ss 4.1, 4.2